Role of parents as a protective factor against adolescent athletes’ doping susceptibility - Blank, C; Leichtfried, V; Müller, D; Schobersberger, W (South African Journal of Sports Medicine, 2015)
Background. Although literature on sports psychology outlines parental influence in various areas, research has not focused on its potential in the framework of doping. Objective. To assess whether parents’ knowledge about doping effects, and their behaviour and beliefs might act as a protecting factor for Austrian junior (14 - 18 years) elite athletes’ doping susceptibility (DS). Methods. Questionnaires were distributed to 1 818 student athletes and their parents. As well as collecting sociodemographic data, information about current sports activity levels and the former sports careers of parents, the following categories were included: (i) knowledge about effects of doping; (ii) parental behaviour; (iii) parental beliefs about athletes’ skills to become a professional athlete; and (iv) DS. Results. In total 527 data sets were entered for analysis. Current state of knowledge was significantly different between mothers (0.72 (0.2)) and fathers (0.76 (0.2)) (p=0.003). Next to situational variables, only fathers’ behaviour, which was moderated by fathers’ beliefs, was a significant predictor of athletes’ DS. Conclusion. Fathers have the potential of acting as a protective factor for DS in athletes, but only if their level of belief is moderate. Doping prevention strategies should include parents, but need to be careful on the role they are planning to fulfil, with an emphasis on soft skills (e.g. communication). Future research might include variables from sports psychology such as motivational climate, goal orientation and belief in success as possible mediators of the influence of parents on their adolescent children in the sport setting.